Amentoflavone attenuates Listeria monocytogenes pathogenicity through an LLO‐dependent mechanism. (28th March 2022) - Tingting, Wang; Tianqi, Fang; Xinyu, Wang; Can, Zhang; Xue, Shen; Xuming, Deng; Jianfeng, Wang
Abstract : Background and Purpose: L. monocytogenes remain a leading cause of foodborne infection. Listeriolysin O (LLO), an indispensable virulence determinant involved in diverse pathogenic mechanisms of L. monocytogenes infection, represents a promising therapeutic target. In this study, we sought to identify an effective inhibitor of LLO pore formation and its mechanism of action in the treatment of L. monocytogenes infection. Experimental Approach: Haemolysis assays were carried out to screen an effective LLO inhibitor. The interaction between candidate and LLO was investigated using surface plasmon resonance and molecular docking. The effect of candidate on LLO‐mediated cytotoxicity, barrier disruption and immune response were investigated. Finally, the in vivo effect of candidate on mice challenged with L. monocytogenes was examined. Key results: Amentoflavone, a natural flavone present in traditional Chinese herbs, effectively inhibited LLO pore formation by engaging the residues Lys93, Asp416, Tyr469 and Lys505 in LLO. Amentoflavone dose‐dependently reduced L. monocytogenes ‐induced cell injury in an LLO‐dependent manner. In the Caco‐2 monolayer model, amentoflavone maintained the integrity of the epithelial barrier exposed to LLO. Amentoflavone inhibited the inflammatory response evoked by L. monocytogenes in an LLO‐dependent manner, and inhibition was attributed to ability to block perforation‐associated K + efflux and Ca 2+ influx. In the mouse infection model, amentoflavone treatment significantly reduced bacterial burden and pathological lesions in target organs, with a significant increase in survival rate. Conclusions and Implications: Amentoflavone reduced the pathogenicity of L. monocytogenes by specifically inhibiting LLO pore formation, and this may represent a potential treatment for L. monocytogenes infection.